Workshop Pemanfaatan Artificial Intelligence (AI) Secara Etis dan Produktif Bagi Pemuda Desa Maduran Lamongan - Novi Ismiasih; Ach. Nurhamid Awalludin; Tito Nur Mustika (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2026)
This mentoring program aims to guide youth in using AI wisely for productive activities, such as creating educational content, developing creative businesses, and digital marketing. The activity was carried out in Maduran Village, Maduran District, Lamongan Regency, East Java, using a Participatory Action Research (PAR) approach that included observation and interviews, planning, implementation, and evaluation. In the initial stage, the team conducted observations and interviews with local youth. Next, in the planning stage, the team coordinated with the village head, prepared materials, and set a schedule for activities. The implementation stage was filled with material on Artificial Intelligence (AI), while the evaluation stage was carried out through training related to AI use. The results of the activity showed that the youth of Maduran Village were able to utilize AI as a supporting tool in education, creativity, and self-development, while still paying attention to moral and social values, and were increasingly critical and selective in using technology